Ythdf is a N6-methyladenosine reader that modulates Fmr1 target mRNA selection and restricts axonal growth in Drosophila - Worpenberg, Lina; Paolantoni, Chiara; Longhi, Sara; Mulorz, Miriam M; Lence, Tina; Wessels, Hans-Hermann; Dassi, Erik; Aiello, Giuseppe; Sutandy, F X Reymond; Scheibe, Marion; Edupuganti, Raghu R; Busch, Anke; et al. (The EMBO journal, 2021)
Abstract N6-methyladenosine (m6A) regulates a variety of physiological processes through modulation of RNA metabolism. This modification is particularly enriched in the nervous system of several species, and its dysregulation has been associated with neurodevelopmental defects and neural dysfunctions. In Drosophila, loss of m6A alters fly behavior, albeit the underlying molecular mechanism and the role of m6A during nervous system development have remained elusive. Here we find that impairment of the m6A pathway leads to axonal overgrowth and misguidance at larval neuromuscular junctions as well as in the adult mushroom bodies. We identify Ythdf as the main m6A reader in the nervous system, being required to limit axonal growth. Mechanistically, we show that the m6A reader Ythdf directly interacts with Fmr1, the fly homolog of Fragile X mental retardation RNA binding protein (FMRP), to inhibit the translation of key transcripts involved in axonal growth regulation. Altogether, this study demonstrates that the m6A pathway controls development of the nervous system and modulates Fmr1 target transcript selection.